Demokratisasi di tingkat lokal: NU dan Muhammadiyah dalam Pilpres 2024 di Kota Salatiga - Sumantri, Imam; Prameswari, Evany Sofia; Priyanto, Agustinus Sugeng (Journal of Political Issues, 2025)
This research examines the phenomenon of democratization at the local level. The political celebration in 2024 is an interesting momentum to see how the dynamics of democratization at the local level. Democracy is a post-reform common spirit that needs to be guarded and improved by various parties, including civil society organizations such as NU and Muhammadiyah. This research aims to obtain an overview and analysis of how the role and existence of NU and Muhammadiyah in contributing to maintaining the quality of community-oriented democracy, especially at the local level. This research uses a descriptive qualitative approach with interview techniques by interviewing several informants and literature and data analysis techniques to analyze the electoral dynamics of NU and Muhammadiyah. The results of research on the role of NU and Muhammadiyah in the contestation of the 2024 presidential election show that political contestation cannot be separated from the influence of NU and Muhammadiyah. The modalities owned by the two largest Islamic organizations in Indonesia still provide a real influence in the electoral process and have implications for the existence of mass organizations. The close affiliation with political parties, especially between Muhammadiyah and the National Mandate Party in Salatiga, also creates strong political relations electorally. Likewise, NU, which has elite-directed solidarity, also increases its existence in the face of political contestation.